New artivist pedagogies for education: evidence of the construction of democratic coexistence and cooperative learning in vulnerable contexts - Holguin Alvarez, Jhon (2020)
The objective of this study is to verify the effects of artivist pedagogies on democratic coexistence and cooperative learning in schoolchildren in vulnerable contexts. The approach was quantitative, experimental design. Two experiments were structured with experimental samples of: a) 85 students from fourth to sixth grade of Primary Education, b) 65 from sixth grade of Primary Education. It was found that: 1) popular artivist pedagogy based on cultural aspects (problems and folklore) develops democratic coexistence in vulnerable contexts, 2) pedagogy based on dactyl theatrical painting develops cooperative learning in a meaningful way and its dimensions, although the interaction Individual is a complex aspect to develop. Therefore, it was determined that popular artivist pedagogy and the experience of dactyl theatrical painting are useful pedagogies for the development of democracy and cooperation for healthy living in contexts of school vulnerability.